Longitudinal study of patients' health-related quality of life using EQ-5D-3L in 11 Swedish National Quality Registers. Issue 1 (6th January 2022) - Teni, Fitsum Sebsibe; Rolfson, Ola; Devlin, Nancy; Parkin, David; Nauclér, Emma; Burström, Kristina
Abstract : Objective: To compare problems reported in the five EQ-5D-3L dimensions and EQ VAS scores at baseline and at 1-year follow-up among different patient groups and specific diagnoses in 11 National Quality Registers (NQRs) and to compare these with the general population. Design: Longitudinal, descriptive study. Participants: 2 66 241 patients from 11 NQRs and 49 169 participants from the general population were included in the study. Primary and secondary outcome measures: Proportions of problems reported in the five EQ-5D-3L dimensions, EQ VAS scores of participants' own health and proportions of participants and mean/median EQ VAS score in the Paretian Classification of Health Change (PCHC) categories. Results: In most of the included registers, and the general population, problems with pain/discomfort were the most frequently reported at baseline and at 1-year follow-up. Mean EQ VAS score (SD) ranged from 45.2 (22.4) among disc hernia patients to 88.1 (15.3) in wrist and hand fracture patients at baseline. They ranged from 48.9 (20.9) in pulmonary fibrosis patients to 83.3 (17.4) in wrist and hand fracture patients at follow-up. The improved category of PCHC, improvement in at least one dimension without deterioration in any other, accounted for the highest proportion in several diagnoses, corresponding with highest improvement in mean EQ VAS score. Conclusions: The study documented self-reported health of several different patient groups using the EQ-5D-3L in comparing with the general population. This demonstrated the important role of patient-reported outcomes in routine clinical care, to assess and follow-up health status and progress within different groups of patients. The EQ-5D-3L descriptive system and EQ VAS have an important role in providing a 'common denominator', allowing comparisons across NQRs and specific diagnoses. Trial registration number: ClinicalTrials.gov (NCT04359628 ).